Numerical methods for particle agglomeration and breakage in lid-driven cavity flows at low Reynolds numbers - Roy, N.; Dürr, R.; Bück, Andreas; Kumar, J.; Sundar, S. (Mathematics and Computers in Simulation, 2022)
In this paper, a rigorous computational study is carried out on the three numerical methods: cell average technique (CAT), weighted finite volume scheme (WFVS), and quadrature method of moments (QMOM). Each method is analyzed to solve the population balance equation coupled with hydrodynamics. Different test cases have been considered for aggregation, breakage, simultaneous aggregation and breakage processes with four different aggregation kernels and uniform breakage function. Both the advantages and disadvantages of those methods are thoroughly investigated for the PBE coupled with hydrodynamics. Based on accuracy and efficiency, it is recommended that the WFVS is a smart choice for computing number density and moments in the case of inhomogeneous PBE.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Cell average technique; Lid-driven cavity; Multi-phase flow; Population balance equation; QMOM